Students’ Environmental Attitudes in the Context of Education for Sustainable Development - Kryazh, Iryna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2021)
The results of two empirical studies of environmental attitudes and pro-environmental behavior of students studying in different fields (samples of 230 and 132 students) are considered. The features of ecological representations of students of ecological specialties at the beginning and at the end of vocational training are determined. Comparison of the effectiveness of professional ecological education and biological education as education for sustainable development indicates a more pronounced impact of ecological education on the formation of pro-environmental attitudes and readiness for pro-environmental behavior. The dynamics of the attitude to global environmental changes among students of the Faculty of Ecology is determined: from consumer attitude to nature, which is combined with a relatively strong belief that money is the key to solving environmental problems, environmental students come to believe in the priority of the world environmental problems. Changes in worldviews are accompanied by an intensification of pro-ecological behavior in everyday life. The impact of ecological education as the education for sustainable development on personality attitudes manifests itself in two ways - in attitudes to the problem of environmental change and in attitudes toward the natural world. The awareness of the importance of anthropogenic environmental change is accompanied by the clarifying of ideas about money as a universal means of solving environmental problems and the awareness of the importance of environmental change not only for humans but also for other species. An important result of these changes is the increased pro-environmental orientation of everyday behavior.